2022
DOI: 10.3390/su14053075
|View full text |Cite
|
Sign up to set email alerts
|

Intelligent Optimized Wind Turbine Cost Analysis for Different Wind Sites in Jordan

Abstract: Choosing the right wind site and estimating the extracted energy of the wind turbines are essential to successfully establishing a wind farm in a specific wind site. In this paper, a method for estimating the extracted energy of the wind farms using several mathematical models is proposed. The estimating method, which was based on five wind turbines, Q1, Q2, Q3, Q4, and Q5 and three wind distribution models, gamma, Weibull, and Rayleigh, was used to suggest suitable specifications of a wind turbine for a speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…GABA accumulation is thought to reduce oxidative damage caused by ROS and thus increase tolerance to oxidative stress [93]. The plant cells decompose the accumulated GABA in the cell through the GABA branch, and the end product formed also acts as the substrate of the TCA cycle.…”
Section: Gaba Is Involved In the Antioxidant Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…GABA accumulation is thought to reduce oxidative damage caused by ROS and thus increase tolerance to oxidative stress [93]. The plant cells decompose the accumulated GABA in the cell through the GABA branch, and the end product formed also acts as the substrate of the TCA cycle.…”
Section: Gaba Is Involved In the Antioxidant Systemmentioning
confidence: 99%
“…The formation of GABA is promoted by activating the Ca 2+ /CaM pathway under UV-B radiation. However, the GABA pathway is blocked in Arabidopsis thaliana after CaM-related mutates, resulting in decreased ROS scavenging ability and resistance to UV-B radiation in seedlings and suggesting that the GABA pathway is involved in the regulation of the plant's antioxidant pathway [93]. Many studies have shown that exogenous GABA treatment can maintain the REDOX state balance at the cell level by affecting the activity of antioxidant-related enzymes in plants to improve their resistance.…”
Section: Gaba Is Involved In the Antioxidant Systemmentioning
confidence: 99%
“…And finally, Jordan has implemented supportive policies and regulations to stimulate investments in renewable energy. Similarly, as stated in [46,47] Jordan was declared one of the top three emerging markets in renewable energy investment in 2018.…”
Section: Role Of Renewable Energy In Co 2 Reductionmentioning
confidence: 90%
“…Moreover, the framework's flexibility allows the customization of blockchain modules, enabling the exploration of different delegate selection methods and consensus mechanisms, to optimize security and efficiency. The utilization of renewable energy resources, particularly wind power, has become essential in addressing environmental concerns related to fossil fuel usage, and the authors in [7] investigated the viability of producing wind energy at several wind farms in Jordan. The study evaluates the expenses related to wind turbine installation and operation by using sophisticated optimization techniques.…”
Section: Related Workmentioning
confidence: 99%